NANOTECHNOLOGY IN CONSTRUCTION MATERIAL SCIENCE: REALITY AND PROSPECTS - S. Zhdanok; B. Khroustalev; E. Batyanowski; S. Leonovich (Наука и техника)
The paper presents information on the beginning, state and prospects of nanotechnology application in the construction industry inBelarus. These technologies are based on the national carbon nano-materials, obtained at theInstituteofHeatand Mass Transfer of NAS of Belarus.